India's FTA with the EU: Opportunities and challenges in services sector - Ankita Dash; Ayona Bhattacharjee (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2024)
Trade in services has been of special interest to both India and the EU as services are a major contributor to GDP and trade flows in the two economies. Steadily rising services trade between India and the EU is, however, characterized by certain peculiarities, which are worth noticing. These include differences across sub-sectors, trading partners, modes of trade and regulatory barriers. These make it worth exploring the potential costs and benefits of increasing trade flows through trade agreements even further while also diversifying the sub-sectors and the destination countries. This is highly relevant as after a gap of nine years, in 2022, India and the EU have recently relaunched talks for an all-inclusive free trade agreement (FTA) in 2022, to cater to their common interests concerning trade in services. [...]
hdl:20.500.12870/6763
Keywords: F13; F14; F15; 330; Trade in services; free trade agreement; European Union; Asia Pacific; technical and trade related services